Body mass index in relation to semen quality, sperm DNA integrity and serum reproductive hormone levels among men attending an infertility clinic - Chavarro, Jorge E. (2009)
OBJECTIVE: To examine the association between body weight and measures of male reproductive potential. DESIGN: Cross-sectional study SETTING: Fertility clinic in an academic medical center. PATIENTS: 483 male partners of subfertile couples. INTERVENTIONS: None MAIN OUTCOME MEASURES: Standard semen analysis, sperm DNA fragmentation and serum levels of reproductive hormones. RESULTS: As expected, BMI was positively related to estradiol levels and inversely related to total testosterone and SHBG levels. There was also a strong inverse relation between BMI and inhibin B levels and a lower testosterone:LH ratio among men with a BMI ≥ 35kg/m(2). BMI was unrelated to sperm concentration, motility or morphology. Ejaculate volume decreased steadily with increasing BMI levels. Further, men with BMI ≥ 35kg/m(2) had a lower total sperm count (concentration × volume) than normal weight men (Adjusted difference in the median [95% CI] = −86 × 10(6) sperm [−134, −37]). Sperm with high DNA damage were significantly more numerous in obese men than in normal weight men. CONCLUSIONS: These data suggest that despite major differences in reproductive hormone levels with increasing body weight, only extreme levels of obesity may negatively influence male reproductive potential.